2019
DOI: 10.1186/s13104-019-4564-x
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and practice of cervical cancer screening and associated factors amongst female students at Wollega University, western Ethiopia

Abstract: Objective This study aimed to assess the knowledge, attitude and practice of cervical cancer screening and associated factors among female students of Wollega University, western Ethiopia in 2017. Results More than half, 54.4%, of participants had heard about cervical cancer and its risk factors. Only 35.8% knew about screening procedures such as pap smear (61.1%) and visual inspection with application of acetic acid (38.8%). Study participants from age of 21 to 25 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
19
4

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 5 publications
6
19
4
Order By: Relevance
“…This is consistent with the study done in Gonder town, North West Ethiopia (78.7%), and Hawassa University Medical and Health Sciences female students (76.8%) [5,14]. This result is higher than the findings in Butajira town (47.6%), Wollega University female students (54.4%), Wolaita zone hospitals (43.1%), Addis Ababa government hospitals (60.8%), Tikur Anbesa Hospital, Ethiopia (21.7%), Nigeria (52.8%), and Cameroon (28%) [5,13,[15][16][17][18][19][20]. However, this finding is lower than the study done among female medical students of Crimea State Medical University in Ukraine (80%) [21].…”
Section: Discussionmentioning
confidence: 86%
“…This is consistent with the study done in Gonder town, North West Ethiopia (78.7%), and Hawassa University Medical and Health Sciences female students (76.8%) [5,14]. This result is higher than the findings in Butajira town (47.6%), Wollega University female students (54.4%), Wolaita zone hospitals (43.1%), Addis Ababa government hospitals (60.8%), Tikur Anbesa Hospital, Ethiopia (21.7%), Nigeria (52.8%), and Cameroon (28%) [5,13,[15][16][17][18][19][20]. However, this finding is lower than the study done among female medical students of Crimea State Medical University in Ukraine (80%) [21].…”
Section: Discussionmentioning
confidence: 86%
“…18 However, it is higher than the reports of a similar study done in western and northern parts of Ethiopia. 12,16 This discrepancy might be due to the majority of participants in this study being from urban areas who may have a higher opportunity of getting information about cervical cancer from mass media and other sources.…”
Section: Discussionmentioning
confidence: 90%
“…10,11 Different studies also revealed that knowledge of women about cervical cancer is very low in Ethiopia. [12][13][14][15][16] The majority of respondents in previous studies have heard about cervical cancer, but not more than half of respondents know what causes cervical cancer and the risk factors associated with the disease. 17,18 Women's age, marital status, occupation, educational status, source of information, knowing someone with cervical cancer and health-seeking behavior were found to be associated with cervical cancer knowledge in Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of cervical cancer screening service utilization reported in the included studies ranges from 0% [ 53 ] to 40.1% [ 56 ]. For the study with zero prevalence, a continuity correction formula that is 0.5 was considered [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…Overall information regarding the prevalence of cervical cancer screening service utilization was obtained from various regions of the country. Ten of the studies involved participants from the Amhara region [35][36][37][38][39][40][41][42][43][44], eleven from the Oromia region [45][46][47][48][49][50][51][52][53][54][55], nine from the SNNPR [56][57][58][59][60][61][62][63][64], four from Tigrai [65][66][67][68], eight from Addis Ababa [69][70][71][72][73][74][75][76], one study involving participants from the Amhara, SNNPR and Afar regions [77], and another study involving participants countrywide [25]. Regarding sampling, all of the studies used the probability sampling technique ( Table 1).…”
Section: Plos Onementioning
confidence: 99%